Program Pengabdian Pembinaan Mental Spiritual Anak Muslim Pinggiran Di Bogor - Alfi Syahriyani; Nawawi Nawawi; Amelia Zakiyyatun Nufus (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
This study aims to provide service by providing guidance to children living on the outskirts of Bogor through mental-spiritual learning for Muslim children. Education is to improve the quality of the implementation and outcomes of education in schools that lead to the achievement of character building and noble character in students, integrated and balanced according to graduate competency standards. To fulfill the education of prospective Indonesian children, it is necessary to pay attention to aspects of the school in terms of learning, a curriculum that is in accordance with existing education standards in Indonesia, and facilities that support learning for students. However, in reality, there is still a lot of education that is lacking in terms of facilities to support learning and also teachers who have not received training to teach according to the appropriate curriculum in Indonesia. Therefore, researchers are interested in doing service by conducting learning coaching for children living on the outskirts of Bogor using the Tilawti method. In this coaching sent 4 teachers with a total of 42 students for 4 months of coaching. This research was conducted at PAUD Nibrosu Lamhariyah (NILAM). The results of this dedication show that 90% of children can follow and can read qiro'ati well and 85% of children can memorize up to 4 short letters fluently and can also memorize short hadiths and ablution prayers and practice.Keywords: Devotion, Development of learning, Religious Learning, Memorization and Recitation, Education. Abstrak Penelitian ini bertujuan untuk memberikan pengabdian dengan memberikan pembinaan pada anak yang tinggal di pinggiran kota Bogor melalui pembelajaran mental spiritual pada anak-anak muslim. Pendidikan merupakan untuk meningkatkan mutu penyelenggaraan dan hasil Pendidikan di sekolah yang mengarah pada pencapaian pembentukan karakter dan akhlak mulia pada peserta didik secara utuh, terpada dan seimbang sesuai standar kompetensi lulusan. Untuk memenuhi pendidikan pada calon anak bangsa Indonesia maka perlu diperhatikan pada aspek sekolah dari segi pembelajaran, kurikulum yang sesuai dengan standar pendidikan yang ada di Indonesia, fasilitas yang mendukung pembelajaran bagi siswa. Namun, pada kenyataannya masih banyak pendidikan yang kurang dalam segi fasilitas dalam mendukung pembelajaran dan juga guru yang belum mendapatkan trainning untuk mengajar sesuai kurikulum yang sesuai di Indonesia. Maka dari itu, peneliti tertarik untuk melakukan pengabdian dengan melakukan pembinaan pembelajaran pada anak-anak di tinggal di pinggir kota bogor dengan menggunakan metode tilawti. Pada pembinaan ini mengirimkan 4 guru dengan total 42 murid selama 4 bulan pembinaan. Penelitian ini dilaksanakan di PAUD Nibrosu Lamhariyah (NILAM). Hasil pengabdian ini menunjukkan 90% anak-anak yang dapat mengikuti dan bisa membaca qiro’ati dengan baik dan 85% anak yang dapat menghafal sampai 4 surat pendek dengan lancar dan juga dapat menghafal hadis-hadis pendek dan doa wudhu dan prakteknya. Kata Kunci: Pengabdian, Pembinaan pembelajaran, Pembelajaran Agama, Menghafal dan Mengaji, Pendidikan